State-of-the-art of historical earthquake research in Fennoscandia and the Baltic Republics - Mäntyniemi, P.; Husebye, E. S.; Kebeasy, T. R. M.; Nikonov, A. A.; Nikulin, V.; Pacesa, A. (Annals of Geophysics, 2004)
We review historical earthquake research in Northern Europe. 'Historical' is defined as being identical with seismic events occurring in the pre-instrumental and early instrumental periods between 1073 and the mid-1960s. The first seismographs in this region were installed in Uppsala, Sweden and Bergen, Norway in 1904-1905, but these mechanical pendulum instruments were broad band and amplification factors were modest at around 500. Until the 1960s few modern short period electromagnetic seismographs were deployed. Scientific earthquake studies in this region began during the first decades of the 1800s, while the systematic use of macroseismic questionnaires commenced at the end of that century. Basic research efforts have vigorously been pursued from the 1970s onwards because of the mandatory seismic risk studies for commissioning nuclear power plants in Sweden, Finland, NW Russia, Kola and installations of huge oil platforms in the North Sea. The most comprehensive earthquake database currently available for Northern Europe is the FENCAT catalogue covering about six centuries and representing the accumulation of work conducted by many scientists during the last 200 years. This catalogue is given in parametric form, while original macroseismic observations and intensity maps for the largest earthquakes can be found in various national publications, often in local languages. No database giving intensity data points exists in computerized form for the region. The FENCAT catalogue still contains some spurious events of various kinds but more serious are some recent claims that some of the presumed largest historical earthquakes have been assigned too large magnitude values, which would have implications for earthquake hazard levels implemented in national building codes. We discuss future cooperative measures such as establishing macroseismic data archives as a means for promoting further research on historical earthquakes in Northern Europe.